Aspirin at any dose above 30 mg offers only modest protection after cerebral ischaemia. Issue 2 (February 1996) - Algra, A; van Gijn, J
Abstract : There is continuing debate about the relative efficacy of low (< 100 mg per day), medium (300 to 325 mg per day), and high (> 900 mg per day) doses of aspirin in patients after a transient ischaemic attack or non-disabling stroke. The purpose of this study was to resolve the issue. Thus a minimeta-analysis was performed on data from 10 randomised trials of aspirin only v control treatment in 6171 patients after a transient ischaemic attack or nondisabling stroke. The data on the trials were listed in an appendix of the report on the second cycle of the Antiplatelet Trialists' Collaboration. There was virtually no difference in relative risk reduction for low, medium, and high doses of aspirin (13%, 9%, and 14% respectively). This equivalence corresponds with the results of the UK-TIA trial in a direct comparison of 300 and 1200 mg. The Dutch TIA trial showed no difference in efficacy of 30 and 283 mg. It is concluded that aspirin at any dose above 30 mg daily prevents 13% (95% confidence interval 4-21) of vascular events and that there is a need for more efficacious drugs.